Anthraquinone-derivatised carbon powder: reagentless voltammetric pH electrodes. - Wildgoose, G; Pandurangappa, M; Lawrence, N; Jiang, L; Jones, T; Compton, R (2003)
A simple pH probe is developed based upon the covalent chemical derivatisation of carbon particles with anthraquinone. The amperometric response of electrodes constructed from this material is examined and shown to produce a Nernstian linear response to pH from 1 to 9, over a range of temperatures from 20 to 70 degrees C, consistent with a two-electron, two-proton electrochemical process.